Development of Balatero Transport Terminal - Abegail M. Malubag (Manila : National University, 2016)
The Philippines as an archipelagic country composed of 7,107 islands and islets with a length of 235,973 square kilometers.
Chapter 1. The Problem and it's settings -- Chapter 2. Research Methodology -- Chapter 3. Terms and Reference -- Chapter 4. Data Gathering, Collection and Analysis of Data -- Chapter 5. Design Framework -- Chapter 6. Translations -- Bibliography -- Appendices
Includes bibliographical references.